Extraction and characterization of bark fibers from Ethiopian Ficus thonningii tree - Biruk Fentahun Adamu; Yohannes Shitahun; Simegn Adane; Terefe Aferu; Kalkidan Tadesse (Discover Materials)
Abstract The growing environmental pollution issues by synthetic textile products demand sustainable natural textile alternatives. This paper aimed at extracting and characterizing a new fiber called Ficus thonningii fiber from Ficus thonningii trees found in Ethiopia to be used as a source of textile fiber for different applications. The study utilized water and chemical extraction with sodium hydroxide methods. Physical, mechanical, and chemical properties such as length, diameter, fineness, tenacity, moisture content, moisture regain, cellulose, hemicellulose, lignin, and ash content were characterized. The results revealed that Ficus thonningii fiber possesses comparable characteristics with jute, sisal, and flax fibers that can be used for different applications. The fiber exhibits tenacity of 39.65 cN, an elongation of 2.60%, a moisture content of 10.78%, and a moisture regain of 11.98% when extracted chemically. While it exhibits a tenacity of 37.83 cN, an elongation of 3.02%, a moisture content of 10.35%, and a moisture regain of 11.02% when extracted using water extraction method. Both extraction methods yield a fiber length of 101.50 mm. The chemical composition of the fiber obtained through water extraction consists of 52.35% cellulose, 19.20% hemicellulose, 17.20% lignin, and 1.20% ash. On the other hand, the chemical extraction method results in a composition of 63.57% cellulose, 16.10% hemicellulose, 12.10% lignin, and 0.83% ash. These results confirm the potential use of Ficus thonningii tree as a valuable source of coarse fibers for various technical textile applications.